The Association of Clinical Symptoms and Coexistent Clinical Conditions with Ophthalmic Manifesting in COVID-19 Patients - Mansour Babaei; Masomeh Bayani; Maral Farzin; Seyed Ahmad Rasoulinejad (Babol University of Medical Sciences, 2022)
Background: The ocular symptoms are common manifestations in coronavirus infectious disease 2019 (COVID-19), which faces secondary complications and therapeutic challenges. Underlying diseases actuate the body to infectious diseases and their related manifestations through the aberration of metabolism and suppressing the immune system. This study aimed to investigate the correlation of underlying diseases and ocular manifestations in COVID-19 patients. Methods: This cross-sectional study was held on 108 hospitalized COVID-19 patients (confirmed by molecular detection) admitted to Rouhani hospital, Babol, Iran. Upon hospitalization, all clinical symptoms and underlying diseases were registered. Detailed clinical examinations regarding ophthalmological protocols were used to investigate the ocular symptoms. All analyses were performed by SPSS, version 25. Results: Our results showed that 26.67% of patients with at least one ocular symptom had hyperlipidemia, while 10.42% of patients without any ocular symptoms had hyperlipidemia (P=0.049). In this study, 97.81% of COVID-19 patients without epiphora had no thyroid disorders (hyper-/hypo-thyroidism), while 82.35% of COVID-19 patients with epiphora had not any thyroid disorders (P=0.012). Also, 75.00% of patients with blurred vision had diabetes mellitus, while 35.00% of patients without blurred vision suffered from diabetes mellitus. This difference was borderline significant (P=0.051). Other results showed that 13.04% of COVID-19 patients with eye redness suffer from myalgia, while 35.29% of patients without eye redness had myalgia (P=0.044). Also, 35.11% of COVID-19 patients without photophobia had myalgia, while no one none of the patients with photophobia had myalgia (P=0.005). Finally, 70.00% of patients with respiratory distress had at least one ocular symptom, while 43.10% of patients without respiratory distress had at least one ocular symptom (P=0.007). Conclusion: Some underlying diseases, e.g., hyperlipidemia, diabetes mellitus, and thyroid disorders, and some clinical symptoms in hospitalized patients, e.g., myalgia and respiratory distress, are correlated with ocular manifestations in COVID-19 patients.